Clinical pathological characteristics and prognosis of orbital myeloid sarcoma-a single center retrospective study with 14 Chinese patients - Tianyi Zhou; Jiaqi Guan; Huijing Ye; Huasheng Yang (Holistic Integrative Oncology)
Abstract Purpose Myeloid sarcoma (MS) is a rare extramedullary tumor of myeloid origin, often underdiagnosed or misdiagnosed, particularly in children. This study aims to evaluate the clinicopathological features, immunophenotypes, therapeutic approaches, and prognosis to enhance patient management. Methods This retrospective, single-center case series examined 14 patients diagnosed with myeloid sarcoma through pathological analysis. Results The median age at diagnosis was 7 years, with a male-to-female ratio of 8:6. The median disease duration at diagnosis was 1 month, and all patients had unilateral eye involvement. The most common presentation was proptosis, followed by restricted eye movement and eyelid swelling. Immunohistochemical analysis revealed that MPO (myeloperoxidase) and lysozyme were the most frequently expressed markers, followed by CD56, α1-antitrypsin (AACT), and CD34. Eleven patients were treated with chemotherapy according to the acute myeloid leukemia (AML) regimen. The median follow-up time for these patients was 13 months. No relapses occurred; one patient died, and three were lost to follow-up. The Kaplan–Meier survival analysis estimated a 5-year overall survival (OS) and event-free survival (EFS) rate of 87.5%. Conclusion Diagnosing myeloid sarcoma (MS) is often challenging. An adequate tumor biopsy and comprehensive immunohistochemical analysis are essential for an accurate diagnosis. Early and consistent systemic chemotherapy can result in long-term survival.